Silicon nitride anti-reflection coatings for CdS/CuInSe2 thin film solar cells by electron beam assisted chemical vapor deposition - Thompson, L. R., author; Rocca, Jorge J., author; Emery, K. A., author; Collins, G. J., author; Mickelsen, R. A., author; Chen, W. S., author; Stanbery, B. J., author; Elsevier Sequoia, publisher (Colorado State University. Libraries, 1985)
The electron beam assisted chemical vapor deposition of silicon nitride anti-reflection coatings onto thin film CdS/CuInSe2 solar cells and the resultant effects on their performance are reported. In some cases large increases in the short circuit current, open circuit voltage and fill factor were observed. The present results are explained by the usual index matching anti-reflection mechanisms and either the passivation of undesirable shunts or improvement of intrinsic diode characteristics.